Analisis Faktor Penyebab Munculnya Kebencian Dikalangan Siswa - Putri Roganda Pane; Melani Limbong; Shelomita A.P Komaling; Surya Yusuf; Roihan Nasution; Abdinur Batubara (Pusat Riset dan Inovasi Nasional, 2024)
Hate among students is an alarming phenomenon in the educational environment. This can range from negative feelings towards fellow students, teachers, or even towards the school itself. This research aims to analyze the factors that cause the emergence of hatred among students. Through surveys and data analysis, factors such as the social environment, personal experiences, and media influence will be explored to understand their impact on hateful behavior among students. It is hoped that the results of this research will provide better insight into the root of the problem of hatred in the school environment and enable the development of effective intervention strategies to overcome this problem.